2000
DOI: 10.1210/endo.141.5.7458
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vascular Endothelial Growth Factors and Their Receptors during Osteoblast Differentiation

Abstract: Endochondral bone formation is regulated by systemically and locally acting growth factors. A role for vascular endothelial growth factor (VEGF) in this process has recently been proposed, because inactivation of VEGF inhibits endochondral bone formation via inhibition of angiogenesis. Despite the known effect of VEGF as specific endothelial growth factor, its effects on osteoblast differentiation have not been studied. We, therefore, examined the expression of VEGF-A, -B, -C, and -D and their receptors in a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
177
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(192 citation statements)
references
References 56 publications
12
177
1
2
Order By: Relevance
“…I Journd qf' Ortl7opardie Research 22 (2004) 73-79 is responsible for stimulation of angiogenesis and prolonged edema [6]. Moreover, VEGF plays an important role in the regulation of bone remodeling by attracting endothelial cells and osteoclasts and by stimulating osteoblast differentiation [3]. Our data (immunohistochemistry and quantitative analysis) confirmed that these membranes continuously secrete this angiogenic factor, which is able to stimulate bone cell differentiation.…”
Section: Discussionsupporting
confidence: 55%
“…I Journd qf' Ortl7opardie Research 22 (2004) 73-79 is responsible for stimulation of angiogenesis and prolonged edema [6]. Moreover, VEGF plays an important role in the regulation of bone remodeling by attracting endothelial cells and osteoclasts and by stimulating osteoblast differentiation [3]. Our data (immunohistochemistry and quantitative analysis) confirmed that these membranes continuously secrete this angiogenic factor, which is able to stimulate bone cell differentiation.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, VEGF detected in ECFC-CM may have contributed significantly to the observed phenomena. VEGF has been reported to induce ALP activity in osteoblasts [34] and enhance osteoblast differentiation [35]. Behr et al also demonstrated that VEGF-A promotes osteogenic and endothelial differentiation [36], thus playing a significant role in skeletal repair [37].Other bone-morphogenic factors such as FGFs, PDGF, oncostatin M, and endoglin have also been reported to induce osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of BMPs to increase the levels of VEGFA mRNA in a concentration and time-dependent fashion has been shown [12,23,51]. Additional synergy between diffusible osteogenic morphogens and proangiogenic factors has been shown to enhance the rate of ectopic bone growth through modulation of angiogenesis, recruitment and induction of local progenitor cells, and enhancement of cell survival [28,42].…”
Section: Functional Protein Expression and Heterotopic Ossificationmentioning
confidence: 99%